Effects of Boron on Learning and Behavioral Disorders in Rat Autism Model Induced by Intracerebroventricular Propionic Acid (Oct, 10.1007/s12011-024-04417-9, 2024) - Alacabey, Nur Akman; Coskun, Devran; Ceribasi, Songul; Atessahin, Ahmet (Springernature, 2025)
[Abstract Not Available]